Metáforas conceptuais atualizadas pelo verbo bater no contexto discursivo das construções lexicais complexas - Barros, Alvanira Lucia de (2009)
This study aims at reflecting on the description of the verb bater, under the approach of the pragmatic-semantic-syntactic aspects. Our proposition is to show a trajectory which starts from the most concrete to the most abstract, considering the contexts into which the verb is inserted and the functions performed by it in its most abstract form. In this sense, the following questions will be answered: 1. Which are the pragmatic-semantic-syntactic relations related to the use of the constructions with the verb bater? 2. Which is the relation between the Complex Lexical Constructions and the metaphor, and how to establish a typology to identify them, considering their supposed literal correlates? 3. How to correlate metaphor vs prototype? In order to treat the phenomenon of the metaphor dealt with in this study, it was adopted the cognitive linguistics of experiential base of Lakoff and Johnson (1980-2002, p. 68), through the interface that this area of study establishes with functional linguistics. Lakoff and Johnson (2002) introduced an important contribution to a new direction of the linguistic studies, when finding that a large part of the statements of everyday language are metaphorical. They affirm that The processes of thought are largely metaphorical . (LAKOFF and JOHNSON, 2002, p. 48). We start from the point of view that it is necessary to consider a methodological posture that might include man as a producer of 11 meaningful speeches. Thus, we believe that understanding the pragmatic-semanticsyntactic relations which are behind the verb, implies seeing and thinking the language in use in a reflexive way, contributing to the process of dynamic construction carried out by and among speakers inserted in social-cultural contexts. The discussion centered on the grammatical focus, though recurrent, still leaves doubts and raises a lot of questioning, due to fluctuations which are presented about the linguistic functions: for example, in the uses of the verb bater, an action verb whose characteristic is always an aspect of activity attached to the subject and, thus, is a verb which comprises an active sentence indicating something performed by part of the subject. However, we notice that there are times when it is performed with the help of a noun, whose result of this conjunction reveals other meanings. They are the uses in which the sense is specific with the verbal form bater plus a noun like in bater-boca, bater com a língua nos dentes, bater de frente, among others. These polysemic uses were investigated in the Folha de S. Paulo corpus, referring to the years 1998, 1999, 2007 and 2008. Such uses present a common form called Complex Lexical Constructions with the verb bater. Our objective was to contribute to the interdisciplinary movement of the Functionalist Theory with the Metaphor Conceptual Theory.